New Early Cretaceous shrimp (Decapoda) from the Sidi Aïch Formation of the Northern Chotts Range, southern Tunisia: Taxonomy, biostratigraphy, and palaeoenvironmental implications. (July 2017) - Boukhalfa, Kamel; Sudarsky, Sergio; Ali, Walid Ben; Feldmann, Rodney M.; Schweitzer, Carrie E.; Soussi, Mohamed
Abstract: The fossil dendrobranchiate shrimp Macropenaeus was originally described from the Upper Cretaceous (Cenomanian) limestones of Hadjoula, northwest Lebanon. A new species, M. sidiaichensis sp. nov., was recovered from the Sidi Aïch Formation in the Northern Chotts Range, southern Tunisia. The Barremian occurrence of the genus in Tunisia suggests that Macropenaeus most likely originated in northern Africa and then migrated to Arabia in the Cenomanian. The association of the fossil shrimp with conchostracans, plant fragments, and fish indicates the interaction of freshwater and marine conditions that characterized the northern African margin as part of widespread coastal complex, paralic environments during the Barremian.